Competencies and training of health professionals engaged in health coaching: A systematic review. (March 2022) - Singh, Harjit K; Kennedy, Gerard A; Stupans, Ieva
Objective: A systematic review was undertaken in order to evaluate the competencies of primary healthcare professionals who are engaged with health coaching patients with chronic health conditions. Methods: The databases CINHAL, EMBASE, PubMed, PsychINFO and SCOPUS were searched to identify peer reviewed papers referring to competencies of health professionals engaged in health coaching. Results: Nine key competencies that health professionals met and which resulted in successful patient outcomes from health coaching were identified. Comparisons of the core health coaching competencies to the competencies for coaches established by the International Coaching Federation and European Mentoring and Coaching Council showed considerable overlap. However, the comparison also reiterated the need for competencies specific to health coaches to be made explicit. Discussion: Health coaching has been shown to improve the health outcomes in patients with chronic health conditions. As such, there is a need to build an evidenced-based competency framework specific to health coaches. At present, the lack of a competency framework on which to base health coach training could significantly impact the outcomes of patients receiving health coaching. Practical implications include improving regulation and quality of health coaching, and more importantly, the health outcomes of patients receiving the service.